Implementation of Thematic Learning in Elementary School - Minda Karina Putri; Otang Kurniaman; Eva Astuti Mulyani (STAI Hubbulwathan Duri, 2023)
Education in elementary schools is very close to learning; for example, thematic learning contained in the 2013 curriculum is very close to the implementation of learning in the classroom. This study aims to describe the implementation of thematic learning in class V of elementary school so that by describing this, the teacher knows practical learning. This type of research is qualitative descriptive. Three data collection techniques are observation, interviews, and documentation. The informants in the study were two homeroom teachers of class V. This research was conducted in a State Elementary School in Pekanbaru. Data analysis uses data reduction techniques, data presentation, and conclusion drawing. The results showed that the thematic learning process includes 1) student-centred. 2) Provide hands-on experience. 3) subject separators. 4) present a concept of various subjects. 5) is flexible. Based on the research results, the implementation of thematic learning is still rudimentary, and there are still those who have not focused on learning mathematics. Nevertheless, most of the research indicators are appropriate.